Effect of Modular Approach Teaching on Achievement of Secondary School Mathematics Students - Umaira Khalil, M. Imran Yousuf (JSE, 2023)
Advancement in teaching techniques has become an essential issue in education. The study ascertains the effects of the modular approach teaching in mathematics for secondary school students. Modules are developed and used by teachers teaching plans by reflecting the skills, abilities and related information in respective unit speaking Current study targeted the module development for teaching of mathematics at grade 10th and to give a comparison between the academic achievement of control & experimental groups treated through traditional & modular approach. The research was conducted by designing an experiment and was based on modules.